Laparoscopic removal of a dermoid cyst in one ovary and an endometrioma in the other: A case report and literature review - Nora Shero; David S. Kim (Elsevier, 2022)
The coexistence of an endometrioma and a dermoid cyst is very uncommon, and there are few case reports of both conditions in the ovaries. A 41-year-old patient presented with left pelvic pain. She was referred with a bilateral pelvic mass. Magnetic resonance imaging (MRI) confirmed a dermoid cyst on the left ovary and an endometrioma on the right side. The patient was taking ibuprofen to relieve pain until the day of surgery. She was advised to proceed with bilateral laparoscopic cystectomy. During the laparoscopic procedure, the inspection showed that ovaries were bilaterally enlarged with cystic appearances. Bilateral ovarian cystectomy was performed in which a left dermoid cyst was removed intact within the ovary followed by a rupture of the endometrioma on the right. The patient tolerated the procedure without any complications. This case of coexistence of endometrioma and dermoid cyst in each ovary, confirmed by MRI due to atypical findings on ultrasound, highlights how efficient removal of both cyst is crucial.